Water Quality River Estuary of Batang Hari, Musi Banyuasin District, the Province of South Sumatera - Ramla Hartini Melo; Edward Alfin; Alim S Niode (Postgraduate, University of Mataram, 2024)
This study aims to determine the water quality of the estuary of the Batangharileko River based on factors of physics, chemistry and biology. The results showed that the water quality of the estuary of the Batangharileko River by physical factors already meets the criteria of raw water for class I, II , III and IV. While chemical parameters already meet the criteria class III water quality standards. Water Appropriation Category I is for the raw water of drinking water, class II for facilities/infrastructure recreation and freshwater fish breeding, class III for fishery cultivation and watering the plants, the Group IV for watering plants. Biological parameters in this case is the abundance, diversity index and dominance index, Batangharileko River estuary has undergone minor contamination although physiologically not appear on macrozoobenthos life